Burning odor-elicited anxiety in OEF/OIF combat veterans: Inverse relationship to gray matter volume in olfactory cortex. (November 2015) - Cortese, Bernadette M.; McConnell, Patrick A.; Froeliger, Brett; Leslie, Kimberly; Uhde, Thomas W.
Abstract: Despite the anatomical overlap between the brain's fear/threat and olfactory systems, a very limited number of investigations have considered the role of odors and the central olfactory system in the pathophysiology of PTSD. The goal of the present study was to assess structural differences in primary and secondary olfactory cortex between combat veterans with and without PTSD (CV + PTSD, CV-PTSD, respectively). An additional goal was to determine the relationship between gray matter volume (GMV) in olfactory cortex and the distressing properties of burning-related odors. A region of interest voxel-based morphometric (VBM) approach was used to measure GMV in olfactory cortex in a well-characterized group of CV + PTSD (n = 20) and CV-PTSD (n = 25). Prior to the MRI exam, combat-related (i.e., burning rubber) and control odors were systematically sampled and rated according to their potential for eliciting PTSD symptoms. Results showed that CV + PTSD exhibited significantly reduced GMV in anterior piriform (primary olfactory) and orbitofrontal (secondary olfactory) cortices compared to CV-PTSD (both p < .01). For the entire group, GMV in bilateral anterior piriform cortex was inversely related to burning rubber odor-elicited memories of trauma (p < .05). GMV in orbitofrontal cortex was inversely related to both clinical and laboratory measures of PTSD symptoms (all p < .05). In addition to replicating an established inverse relationship between GMV in anxiety-associated brain structures and PTSD symptomatology, the present study extends those findings by being the first report of volumetric decreases in olfactory cortex that are inversely related to odor-elicited PTSD symptoms. Potential mechanisms underlying these findings are discussed. Graphical abstract: Highlights: Combat veterans commonly report odors associated with their traumatic experiences. Volumetric imaging revealed insult of the olfactory cortex in combat-related PTSD. Olfactory cortical atrophy was inversely related to odor-elicited PTSD symptoms.